The Disease Burden of Respiratory Syncytial Virus in Infants - Martinon-Torres, F (LIPPINCOTT WILLIAMS & WILKINS, 2023)
Purpose of reviewTo describe the current global burden of respiratory syncytial virus (RSV) in infants and its implications for morbidity, health resources and economic costs.Recent findingsNew prophylactic therapies are on the horizon for RSV in the form of long-acting monoclonal antibodies suitable for healthy infants and maternal immunizations.SummaryDespite being responsible for significant global infant morbidity and mortality, until recently there have been no effective therapeutics available for healthy infants to protect them from RSV. Several new drugs are likely to be available within the next few years which could help relieve a huge burden on healthcare systems over the coming winters.